Effect Of Thixoforming On The Wear Properties Of Al-Si-Cu Aluminum Alloy - Alhawari, Khaled Salem; Omar, Mohd Zaidi; Ghazali, Mariyam Jameelah; Salleh, Mohd Shukor; Abdulrazaq, Mohammed Naser (Penerbit UTM Press, 2017)
In this study a hypoeutectic Al-6Si-3Cu aluminium alloy was synthesized using two different routes: the thixoforming process and the conventional mould casting process. The microstructural features, hardness and wear behavior of thixoformed alloy have been evaluated and compared with that of as-cast alloy. Cooling slope method was used to produce the non-dendritic microstructure feedstock for thixoforming. Thixoforming was carried out at 50% liquid fraction. The dry sliding wear behaviour of the produced alloys was investigated under two loads; namely, 10 and 50 N and 1m/s sliding speed for 9 km sliding distance. The thixoformed alloy exhibited globular primary phase morphology with fine and uniform distributed Si and intermetallic particles. On the contrary, dendritic primary phase, coarse flaky silicon particles and segregated microstructure has been observed in conventional cast alloy. Thixoformed alloy exhibited improvement in the wear resistance in comparison to the conventional cast alloy, which may be attributed to the microstructural enhancement resulting in improved hardness. The thixoformed samples displayed lower volume loss of ~16.20 mm3 and ~42.40 mm3 at loads of 10 and 50 N respectively compared with that of conventional cast samples. On the basis of observations and analyses on the wear rates and worn surfaces, the wear mechanism of the alloys was dominantly controlled by abrasive, adhesive and minor delamination.